Liver slice culture as a model for lipid metabolism in fish - Thomas N. Harvey; Simen R. Sandve; Yang Jin; Jon Olav Vik; Jacob S. Torgersen (PeerJ, 2019)
Hepatic lipid metabolism is traditionally investigated in vitro using hepatocyte monocultures lacking the complex three-dimensional structure and interacting cell types essential liver function. Precision cut liver slice (PCLS) culture represents an alternative in vitro system, which benefits from retention of tissue architecture. Here, we present the first comprehensive evaluation of the PCLS method in fish (Atlantic salmon, Salmo salar L.) and validate it in the context of lipid metabolism using feeding trials, extensive transcriptomic data, and fatty acid measurements. We observe an initial period of post-slicing global transcriptome adjustment, which plateaued after 3 days in major metabolic pathways and stabilized through 9 days. PCLS fed alpha-linolenic acid (ALA) and insulin responded in a liver-like manner, increasing lipid biosynthesis gene expression. We identify interactions between insulin and ALA, where two PUFA biosynthesis genes that were induced by insulin or ALA alone, were highly down-regulated when insulin and ALA were combined. We also find that transcriptomic profiles of liver slices are exceedingly more similar to whole liver than hepatocyte monocultures, both for lipid metabolism and liver marker genes. PCLS culture opens new avenues for high throughput experimentation on the effect of “novel feed composition” and represent a promising new strategy for studying genotype-specific molecular features of metabolism.